Differentiation between enamines and tautomerizable imines in the oxidation reaction with TEMPO - Xiaoming Jie (Nature Portfolio, 2018)
Tautomerization of imines into enamines is the basis of their similar reactivity; however, minor structural changes may lead to different outcomes. Here, the authors show that the reaction of cyclohexanone and amines in presence of TEMPO affords either α-amino-enones or arylamines depending on the intermediate imine structure.